Pengaruh Motivasi, Disiplin Kerja, Dan Kemampuan Kerja Terhadap Peningkatan Kualitas Pelayanan Dinas Perikanan Kabupaten Brebes - Irmawati Dewi; Ari Kristiana; Muhammad Syaifulloh (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to examine the influence of motivation variables, work discipline and work ability on improving service quality at the Brebes Regency Fisheries Service. This research uses a quantitative approach with multiple linear regression analysis methods. The research sample consisted of 43 employees of the Brebes Regency Fisheries Service who were selected using saturated sampling. The results of the analysis show that the motivation variable has a positive and significant influence on service quality (t = 2.719 > t table = 2.023, sig = 0.010 < 0.05). The work discipline variable also has a positive and significant effect on service quality (t count = 4,180 > t table = 2,023, sig = 0.000 < 0.05). Meanwhile, the work ability variable shows a positive and significant influence on service quality (t count = 2.648 > t table = 2.023, sig = 0.012 < 0.05). Simultaneously, these three variables have a significant effect on service quality, with a calculated F value of 24,378 which is greater than F table 2.84 (sig = 0.000 < 0.05). This research suggests that the Brebes Regency Fisheries Service improve motivation, discipline and work skills training programs to improve service quality. It is hoped that these findings can become a reference for other government agencies in efforts to improve the quality of public services.